Fire keeper's daughter - Boulley, Angeline; HPL Readers Services (New York : Henry Holt and Company, 2021)
"Daunis Fontaine has never quite fit in, either in her hometown or on the nearby Ojibwe reservation. She dreams of college, but when her family is struck by tragedy she puts her future on hold to care for her fragile mother. The only bright spot is meeting Jamie, a new recruit on her brother Levi's hockey team. When Daunis witnesses a shocking murder, she reluctantly agrees to go undercover, drawing on her knowledge of chemistry and Ojibwe traditional medicine to track down the source of a new drug. How far will she go to protect her community, if it threatens to tear apart the only world she's ever known?" -- adapted from jacket.
Ideal for your Book Club or Reading Group. This kit includes a nylon Halifax Public Libraries bag with 10 copies of Angeline Boulley's "Firekeeper's daughter", along with author and title information, and a list of discussion questions. The kit is available to borrow for 6 weeks.
Includes bibliographical references (page 491).
Winner of the Michael L. Printz Award for Excellence in Young Adult Literature, 2022.
YF / NAT dl Cki: Includes 10 books and information folder in 2 HPL branded nylon bags.
Keywords: Lesbian teenagers -- Fiction; Drugs -- Fiction; Undercover operations -- Fiction; Racially mixed people -- Fiction; Ojibwa Indians -- Fiction; Michael L. Printz Award; Michigan -- Fiction; Suspense fiction; Book Club Kit